AIAA Guidance, Navigation, and Control Conference 2010
DOI: 10.2514/6.2010-7863
|View full text |Cite
|
Sign up to set email alerts
|

Developing Operator Models for UAV Search Scheduling

Abstract: With the increased use of Unmanned Aerial Vehicles (UAVs), it is envisioned that UAV operators will become high level mission supervisors, responsible for information management and task planning. In the context of search missions, operators supervising a large number of UAVs can become overwhelmed with the sheer amount of information collected by the UAVs, making it difficult to optimize the information collection or direct their attention to the relevant data. Novel decisionsupport methods that account for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…48 Increasing automation transparency may be difficult with the use of meta-heuristic and auction algorithms, whereas deterministic solvers such as greedy algorithms often emulate the method by which humans would choose to solve the problem. 49 with an "inferior," but understandable algorithm perform better than a human operator collaborating with a more "advanced" but less predictable and more opaque algorithm? Finally, one of the largest issues with the adoption of stochastic algorithms for UV scheduling may be regulatory 50 -how does one certify that an algorithm with no guarantee of repeatability is safe or ready for deployment in safety critical missions?…”
Section: B Guarantees Of Optimalitymentioning
confidence: 95%
“…48 Increasing automation transparency may be difficult with the use of meta-heuristic and auction algorithms, whereas deterministic solvers such as greedy algorithms often emulate the method by which humans would choose to solve the problem. 49 with an "inferior," but understandable algorithm perform better than a human operator collaborating with a more "advanced" but less predictable and more opaque algorithm? Finally, one of the largest issues with the adoption of stochastic algorithms for UV scheduling may be regulatory 50 -how does one certify that an algorithm with no guarantee of repeatability is safe or ready for deployment in safety critical missions?…”
Section: B Guarantees Of Optimalitymentioning
confidence: 95%
“…In [2], a decision support system is developed to aid a single operator manage information received by multiple UAVs. Savla et al developed a queuing model in which UAVs and human are servers and targets appear over time [20].…”
Section: Literaturementioning
confidence: 99%
“…A number of human-machine interaction strategies are proposed in [17] for a single operator-multiple heterogeneous vehicles scenario. In [18], a decision support system for sequential visual search tasks is presented while the effectiveness of the system is validated by human-subject experiments. It is shown that the human operator performance improves under the decision support system with automated algorithmic aids.…”
Section: B Literature Reviewmentioning
confidence: 99%